Cappable recursively enumerable degrees and Post's program - Ambos-Spies, Klaus; Nies, André (Archive for mathematical logic, 1992)
We give a simple structural property which characterizes the r.e. sets whose (Turing) degrees are cappable. Since cappable degrees are incomplete, this may be viewed as a solution of Post's program, which asks for a simple structural property of nonrecursive r.e. sets which ensures incompleteness.